Pengamanan Virtual Network Berbasis OpenVPN Dengan Kerberos Pada Ubuntu 14.04 LTS - Bima, Angga Satria; , Helman Muhammad, S.T., M.T (2016)
Virtual Private Network is one of the solutions to secure data which reside in a local network that is connected to a public network. Kerberos may be utilized to increase the security on the protocol side, hence creating double security on the data path and protocol. In this research Ubuntu 14.04 LTS was chosen as virtual server for deploying Virtual Private Network and Kerberos, which was then tested against siniffing attacks and monitored with Wireshark. The result shows that the double security has been materialized.